THE CHANGING LANDSCAPE OF FIN-TECH IN THE DIGITAL ERA - K.M. Poornima , Dr S. Chitra (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The seamless integration of technology in every spectrum of finance is the result of innovation in both finance and technology. Starting with automation of accounting, enterprise resource planning, complete management information system and banking applications. Fin-tech has become all pervasive, in the new millennium the progress has been tremendous on account of the internet supremacy and dynamic evolution of Artificial Intelligence (AI) and Machine Learning (ML), Big Data, Mobile phone interface and robotic process automation have all taken fin-tech to the next level and there is a rapid change of landscape in this area. This disruptive research aims to bring out the emerging four area in fin-tech that may derive businesses in the next decade. Using a combination of primary and secondary data the study identifies the emerging technologies and their applications in the field of finance including micro wealth management, hyper personification of big data and mobile phone interface. The study reveals that fin-tech is a potential technology disrupter that may change the way people and institutions handle the function of finance.